A Helical Polyphenylacetylene Having Amino Alcohol Moieties Without Chiral Side Groups as a Chiral Ligand for the Asymmetric Addition of Diethylzinc to Benzaldehyde. Issue 8 (12th May 2015) - Liu, Lijia; Long, Qing; Aoki, Toshiki; Zhang, Geng; Kaneko, Takashi; Teraguchi, Masahiro; Zhang, Chunhong; Wang, Yudan
Abstract One‐handed helical polyphenylacetylenes having achiral amino alcohol moieties, but no chiral side groups, were synthesized by the helix‐sense‐selective copolymerization of an achiral phenylacetylene having an amino alcohol side group with a phenylacetylene having two hydroxyl groups. Since the resulting helical copolymers were successfully utilized as chiral ligands for the enantioselective alkylation of benzaldehyde with diethylzinc, we can conclude that the main‐chain chirality based on the one‐handed helical conformation is useful for the chiral catalysis of an asymmetric reaction for the first time. The enantioselectivities of the reaction were controlled by the optical purities of the helical polymer ligands. In addition, the polymer ligands could be easily recovered by precipitation after the reaction. Chirality 27:454–458, 2015. © 2015 Wiley Periodicals, Inc.